2019
DOI: 10.1111/pace.13827
|View full text |Cite
|
Sign up to set email alerts
|

Early repolarization pattern in an ethnically diverse population: Increased risk in Hispanics

Abstract: Background: Early repolarization (ER) pattern on ECG is associated with an increased mortality inCaucasians. This study analyzed the association between ER pattern and all-cause mortality in a population of multiple ethnicities. Methods:A total of 20 000 individuals were randomly selected and their ECGs were analyzed for ER pattern using the 2015 consensus: end-QRS notching or slurring with a J-point (Jp) ≥0.1 mV in contiguous inferior or lateral leads. Exclusion criteria were age <18, QRS duration of ≥120 ms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
(26 reference statements)
1
5
0
Order By: Relevance
“…The study agrees with prior studies in African‐American population that did not show higher overall cardiac mortality . In this study, Leiderman et al are the first to report significance in mortality in the Hispanic population, especially in those with Jp ≥0.2 mV with horizontal/downsloping ST morphologies, and in inferior leads (type 2 ER) compared to lateral leads (type 1 ER). These parameters have been previously studied and have been associated with higher risk of mortality.…”
Section: Genes Linked To Early Repolarizationsupporting
confidence: 92%
See 1 more Smart Citation
“…The study agrees with prior studies in African‐American population that did not show higher overall cardiac mortality . In this study, Leiderman et al are the first to report significance in mortality in the Hispanic population, especially in those with Jp ≥0.2 mV with horizontal/downsloping ST morphologies, and in inferior leads (type 2 ER) compared to lateral leads (type 1 ER). These parameters have been previously studied and have been associated with higher risk of mortality.…”
Section: Genes Linked To Early Repolarizationsupporting
confidence: 92%
“…The study agrees with prior studies in African-American population that did not show higher overall cardiac mortality. 17 In this study, Leiderman et al 19…”
Section: Mortality Risk Of Early Repolarization Patternmentioning
confidence: 69%
“…[ 33 ] Six studies reported the prevalence in the Asia, including 3 in China [ 32 , 35 , 44 ] and 1 each in Japan, [ 8 ] Korea, [ 15 ] and Thailand. [ 34 ] Eight studies reported the prevalence in the United States [ 16 , 20 , 25 , 28 , 37 , 40 , 42 , 45 ] and 1 each study reported the prevalence in Madagascar, [ 27 ] Egypt, [ 29 ] and Latin America. [ 26 ] The worldwide prevalence map of ERP by region was shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the 29 included studies involving a total general population of 182,135 subjects are shown in Table 1. Of the 29 studies, [5,8,15,16,19–21,24–45] 14 studies (48.3%) reported the prevalence in the Europe, including 3 in France, [5,30,38] 3 in Germany, [19,31,43] 3 in Finland, [21,24,40] 2 in the UK, [36,41] 2 in Italy, [27,39] and 1 in Spain [33] . Six studies reported the prevalence in the Asia, including 3 in China [32,35,44] and 1 each in Japan, [8] Korea, [15] and Thailand [34] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation